The Role of Imagery in Film Creation (on the Example of Technical Images in Western Sci-Fi Films) - S. A. Pankratova (Дискурс)
Introduction. The paper deals with the peculiarities of the technical image nomination in western sci-fi films. The aim of the paper is to analyse the means of rendering of the technical imagery in modern films. The scientific topicality is in treating the subject of the paper in the light of the modern cognitive approach to image conceptualization, which is studied with the aim of demonstrating the individual specific picture of the world of the film creation. The study is centered around technical images from western films about computers and mechanisms. The topicality of the study is defined by the invariably high level of popularity of the technical sphere in the modernity by comparison with other (natural, biological) semantic spheres.Methodology and sources. The paper makes use of specific linguistic methods of observation, description, qualitative count and the universal method of comparison. The unique method of conceptual modelling allows to reconstruct reality objects behind certain technical images. The method “from the opposite” questions the trend to activate certain thematic fields in image nomination whilst other are left unheeded. The fact basis of the study is formed from more than 500 technical images of the modern English language, found by means of solid selection from more than 30 feature film scripts, dealing with the world of technology based on the site scripts.com.Results and discussion. The analysis of technical imagery in western film discourse was carried out with the help of cognitive and discoursive methods, disclosing evaluational statements of film characters aimed at solving the topical issues in films. The analysis demonstrated that thanks to its implicit nature the image is able to render the emotional condition, to give direction to thought process, to provide wide program of information processing accompanied by the freedom of choice. Evaluational categories of expressiveness and imagery are used by directors and scriptwriters in assessment and adaptation of the collective knowledge and schemes in personal conceptual system of the film character in the process of the rendering of the personal vision of the world.Conclusion. The use of cognitive and discoursive methods allowed to identify the role of images in film production. The image doesn’t belong to the secondary background knowledge, it is situated in the middle between the secondary and the significant, enabling the knowledge with the element of emotion. The implicitness of images in films stimulates thinking, directs the search of lost plot lines, lays the basis for the disclosure of the director’s vision. The image allows the viewer to be active and the process of viewing become a kind of common creation, common drawing of the image.